Comparison of four diluents for the retriever dogs semen preservation - Wicaksono, A.; Arifiantini, R.I. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
The quality of chilled semen depends on the composition of diluent. The choice of the buffer, anti-cold shock and nutrition sources can be the first decision in order to choose appropriate diluents. Nowadays a lot of diluent are used for canine semen preservation such as Tris buffer and Citrate buffer. This study was aimed to observe the differences of diluent for preserving Retriever dog spermatozoa. The semen sample collected from four Retriever dogs with three times repetition. The semen was evaluated macro-and microscopically. The semen with >70% sperm motility was divided into four tubes and diluted with diluter 1 (P1), diluter: P2, P3 and P4 (modified P3). The diluted semen was divided into two tubes and each sample was stored at room and 50C temperature. The viability of chilled semen was observed every 3 hours at room temperature and 12 hours at 50C. The result showed that P2 keep the sperm viability better than the other diluents. On 50C at 24 hours storage P2 showed the highest motile and live sperm percentage (46.25 ± 0.22%; 57.11 ± 0.25%). In room temperature at 6 hours P2 showed the highest motile and live sperm percentage (40.94 ± 0.20%; 52.65 ± 0.23%). It is concluded that P2 can keep the sperm viability by 84 hours of 50C and 21 hours at room temperature. Key Words: Diluents, Dog Sperm, Retriever